Optimalisasi Digital Marketing melalui Pelatihan Fotografi Produk dan Penggunaan E-Commerce di KWT Ceria Boyolali - Firsyawardana, Muhamad Reznu; Andreas, Rino; Kriskartika, Septi Anggita; Pratama, Rony Kurniawan; Umaiyah, Siti (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
The urgency of improving product marketing effectiveness in Musuk Village, Boyolali, arises because the Ceria Women Farmers Group (KWT Ceria) has been relying on face-to-face sales with limited reach and minimal visual appeal to attract potential buyers. The goal of this training is to enhance the knowledge and skills of KWT Ceria members in product photography and the use of e-commerce platforms to expand market access. The methods applied in this training include interactive lectures on the basic principles of product photography and digital marketing strategies, demonstrations of e-commerce applications, as well as hands-on practice in product photography and uploading photos to online platforms. The post-training evaluation results show a significant increase in participants' knowledge, enhanced technical skills in product photography, and deliverables such as a digital product catalog and e-commerce accounts. The findings demonstrate that product photography and digital marketing training can strengthen the competitive edge of KWT Ceria in the digital era. This training not only provided technical skills but also improved the members' ability to utilize technology to market products more widely and efficiently.